2019
DOI: 10.1186/s13568-019-0854-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of chalcone isomerase from Carthamus tinctorius

Abstract: Flavonoid is one of the widespread groups of plant secondary metabolites that provide several health benefits. However, the explicit mechanism of flavonoid biosynthesis in plants largely remains unclear. Chalcone isomerase an important class of enzyme presents crucial role during flavonoid metabolism in many plants. Here, we isolated the full-length cDNA (1161 bp) of a novel Chalcone Isomerase from safflower encoding 217 amino acid polypeptide using oligos from 5′ and 3′ ends. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Studies have found that type I CHIs are the bona fide CHIs with enzymatic activity converting naringenin chalcone to naringenin (Ni et al, 2020); overexpression of type I CHI genes increases the content of total flavonoid in various plants (Muir et al, 2001;Li et al, 2006;Park et al, 2011;Chung et al, 2019;Liu et al, 2019;Sun W. et al, 2019;Dare et al, 2020;Ni et al, 2020). In this study, three CHI Type I members were found in D. cambodiana; DcCHI1 may be the key isoform involved in flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 47%
“…Studies have found that type I CHIs are the bona fide CHIs with enzymatic activity converting naringenin chalcone to naringenin (Ni et al, 2020); overexpression of type I CHI genes increases the content of total flavonoid in various plants (Muir et al, 2001;Li et al, 2006;Park et al, 2011;Chung et al, 2019;Liu et al, 2019;Sun W. et al, 2019;Dare et al, 2020;Ni et al, 2020). In this study, three CHI Type I members were found in D. cambodiana; DcCHI1 may be the key isoform involved in flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 47%
“…It was suggested that AhCHS could be the first key DEG for early color differentiation in peanut testa, with these results being consistent with previous studies ( Hu et al, 2021a ). It was also found that the expression level of CHI was positively correlated with anthocyanin content ( Liu et al, 2019 ), and that CHI activity could increase the flavonoid content ( Li et al, 2006 ). Additionally, even though AhCHI was consistently highly expressed in Z1, it was first highly expressed in Z2.…”
Section: Discussionmentioning
confidence: 99%
“…CmCHS , CmCHI , and CmF3′H are highly expressed during early developmental stages, whereas, CmF3H , CmDFR , CmANS , and CmUFGT are expressed in a coordinative manner throughout all stages of ray floret development [ 48 ]. The pattern of CmCHI expression was found to be similar among different cultivars with different anthocyanin contents [ 49 , 50 ]. The high expression levels of CmDFR revealed a correlation between anthocyanin accumulation and pink- and white-colored chrysanthemum [ 32 ].…”
Section: Genes Involved In Anthocyanin Biosynthesismentioning
confidence: 99%